Relevance of a preventive model of osteomyoarticular lesions in young adults - Ernesto Sánchez Hernández; Gertrudis de la Torre Vega; Lisbet Estrada Ladoy; Mislay Rodríguez García; Nadina Travieso Ramos (Medisan, 2024)
Introduction: Osteomyoarticular lesions among young people that render services for the defense are related to risk factors. The use of preventive models bases its approach on the identification of risk and development of actions for its prevention. Consent methods are used for their validation and participative models, interpretative and constructivist valuations on their processes back the evaluation of its impact.